2015
DOI: 10.4314/ahs.v15i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of latent Tuberculosis among adolescents in rural Eastern Uganda

Abstract: Background: Latent Tuberculosis treatment is a key tuberculosis control intervention. Adolescents are a high risk group that is not routinely treated in low income countries. Knowledge of latent Tuberculosis (TB) burden among adolescents may influence policy. Objectives: We determined the prevalence and risk factors of latent TB infection among adolescents in rural Uganda. Methods: We analyzed baseline data from a study that assessed the prevalence and incidence of Tuberculosis disease among adolescents. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 17 publications
5
23
4
1
Order By: Relevance
“…On the other hand, these results are consistent with studies conducted in 14 . However, the prevalence of LTBI in the present study was 14.7%, which was significantly lower than high risk health care worker populations in Thailand (63%), Uganda (57%), and the Netherlands (41%), which is justifiable due to the fact that Iran is an intermediate region in terms of endemicity 15,16 . The results of the present study showed that the incidence of LTBI in technicians (1.82%) and nurses (6.63%) was higher than other hospital personnel.…”
Section: Discussioncontrasting
confidence: 68%
“…On the other hand, these results are consistent with studies conducted in 14 . However, the prevalence of LTBI in the present study was 14.7%, which was significantly lower than high risk health care worker populations in Thailand (63%), Uganda (57%), and the Netherlands (41%), which is justifiable due to the fact that Iran is an intermediate region in terms of endemicity 15,16 . The results of the present study showed that the incidence of LTBI in technicians (1.82%) and nurses (6.63%) was higher than other hospital personnel.…”
Section: Discussioncontrasting
confidence: 68%
“…The reported prevalences in three studies [1315] were higher than those of the current Iranian meta-analysis. Only the Gambian survey [16] showed lower estimates than Iran.…”
Section: Discussioncontrasting
confidence: 68%
“…Notably, although a post-exposure vaccination campaign among South African adolescents would include a greater proportion of IGRA-positive individuals than in China (Gao et al, 2015;Bunyasi et al, 2019), half of adolescent vaccinees would still be Mtb-uninfected. Lower prevalence rates of Mtb infection among adolescents in e.g., Kenya (32%) (Nduba et al, 2019) and Uganda (16%) (Mumpe-Mwanja et al, 2015), would favor a preexposure rather than a post-exposure approach for adolescents in these and other countries with lower Mtb transmission rates (Gao et al, 2015). This distinction is important, because TB FIGURE 1 | Target populations for new TB vaccines include Mtb-uninfected (pre-exposure) and Mtb-infected, TB diseased, and treated individuals (post-exposure).…”
Section: Target Populations For a New Tuberculosis Vaccinementioning
confidence: 99%
“…It is not known whether a two-dose M72/AS01 E vaccination regimen offers the same level of protection to IGRA-negative and IGRA-positive individuals; whether priming by Mtb infection is a necessary component of the M72/AS01 E vaccine-induced protection observed in IGRA-positive people; and if so, whether adolescent BCG revaccination could fulfill that priming function prior to M72/AS01 E vaccination of IGRA-negative adults. The issue of efficacy in IGRA-negative individuals is particularly crucial for age-targeted vaccination of children and adolescents, who have lower prevalence rates of Mtb infection than adults (Mahomed et al, 2006(Mahomed et al, , 2011b, and for mass campaigns in countries such as Kenya (Nduba et al, 2019), Uganda (Mumpe-Mwanja et al, 2015), and China (Gao et al, 2015), where the majority of the adult population is Mtb-uninfected. Efficacy data for pre-exposure vaccination of IGRA-negative populations will likely be crucial to motivate the health system use case, even in high TB burden countries, and any Phase 3 trial should be adequately powered to provide a definitive answer to this question.…”
Section: Post-exposure Approaches To Prevention Of Disease (Pod) In Amentioning
confidence: 99%